“Weaving all of them together”: How Writing Majors Talk about Creative Writing - T J Geiger (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
The labels “creative” and “creative writing” serve several purposes in the discourses of undergraduate writing majors. In a study of students in two writing major programs, students often exerted significant effort to negotiate among diverse writing experiences and to integrate different understandings of writing. Their efforts mirror scholars’ conversations about negotiation and integration at the level of curricula and programs. Writing majors in this study raised issues relevant to the well-established curricular domains of theoretical knowledge, professional expertise, and civic action. They explained their insights using a mix of idiosyncratic, institutional, and disciplinary language that frequently relied on forms of “’not’ talk” (Reiff and Bawarshi). One term around which much of their blended-language and ‘not’ talk centered was “creative.” Students used the label “creative” to mean writing fiction and poetry, personal expression, creative nonfiction prose, nonacademic discourse, and flexibility in style and genre. Frequently, these uses were mixed together or slipped casually from one to another. These findings suggest that as students engage with disciplinary purposes for writing in the major, they draw from a range of literacy discourses to negotiate among and to integrate diverse forms of knowledge.
Keywords: JAEPL